Anti-miR-96 and Hh pathway inhibitor MDB5 synergistically ameliorate alcohol-associated liver injury in mice. (April 2023) - Kumar, Virender; Sethi, Bharti; Staller, Dalton W.; Xin, Xiaofei; Ma, Jingyi; Dong, Yuxiang; Talmon, Geoffrey A.; Mahato, Ram I.
Abstract: Alcohol-associated liver disease (ALD) and its complications are significant health problems worldwide. Several pathways in ALD are influenced by alcohol that drives inflammation, fatty acid metabolism, and fibrosis. Although miR-96 has become a key regulator in several liver diseases, its function in ALD remains unclear. In contrast, sonic hedgehog (SHH) signaling has a well-defined role in liver disease through influencing the activation of hepatic stellate cells (HSCs) and the inducement of liver fibrosis. In this study, we investigated the expression patterns of miR-96 and Hh molecules in mouse and human liver samples. We showed that miR-96 and Shh were upregulated in ethanol-fed mice. Furthermore, alcoholic hepatitis (AH) patient specimens also showed upregulated FOXO3a, TGF-β1, SHH, and GLI2 proteins. We then examined the effects of Hh inhibitor MDB5 and anti-miR-96 on inflammatory and extracellular matrix (ECM)-related genes. We identified FOXO3 and SMAD7 as direct target genes of miR-96. Inhibition of miR-96 decreased the expression of these genes in vitro in AML12 cells, HSC-T6 cells, and in vivo in ALD mice. Furthermore, MDB5 decreased HSCs activation and the expression of ECM-related genes, such as Gli1, Tgf-β1, and collagen. Lipid nanoparticles (LNPs) loaded with the combination of MDB5, and anti-miR-96 ameliorated ALD in mice. Our study demonstrated that this combination therapy could serve as a new therapeutic target for ALD.